Commentary on the Second World Congress on Medical Education - García Rosell, O. (1959)
In 1953 took place in London the First World Congress on Medical Education convened by the World Medical Association, which he attended as a representative of our faculty, our present Dean, Dr. Alberto Hurtado, who with the ability and accuracy that are characteristics yield released from the same place, all the importance and significance of that event.